1999
DOI: 10.1086/514284
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Ebola Hemorrhagic Fever: A Study of Risk Factors in Family Members, Kikwit, Democratic Republic of the Congo, 1995

Abstract: The surviving members of 27 households in which someone had been infected with Ebola virus were interviewed in order to define the modes of transmission of Ebola hemorrhagic fever (EHF). Of 173 household contacts of the primary cases, 28 (16%) developed EHF. All secondary cases had direct physical contact with the ill person (rate ratio [RR], undefined; P õ .001), and among those with direct contact, exposure to body fluids conferred additional risk (RR, 3.6; 95% confidence interval [CI], 1.9 -6.8). After adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
330
2
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(356 citation statements)
references
References 8 publications
13
330
2
5
Order By: Relevance
“…Our secondary attack risk estimate of 21% is within the range reported for Ebola outbreaks for comparable types of contacts: Ebola-Zaire, Kikwit, 1995, household contacts 16% ( 5 ); Yambuku, 1976, close relatives, 20% ( 9 ); Ebola-Sudan, Nzara, 1979, family members with physical contact including nursing 31% ( 10 ) Our estimate is much higher than the 2.5% reported for Ebola-Sudan, Uganda, 2000 ( 11 ); however, the Ugandan estimate may have included persons who merely stayed in the same house as a patient without reporting physical contact. The secondary and tertiary attack risks in our study were found to be virtually identical, 21% and 19%, respectively; thus no evidence suggested that Marburg virus loses infectivity by repeated passages through humans.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our secondary attack risk estimate of 21% is within the range reported for Ebola outbreaks for comparable types of contacts: Ebola-Zaire, Kikwit, 1995, household contacts 16% ( 5 ); Yambuku, 1976, close relatives, 20% ( 9 ); Ebola-Sudan, Nzara, 1979, family members with physical contact including nursing 31% ( 10 ) Our estimate is much higher than the 2.5% reported for Ebola-Sudan, Uganda, 2000 ( 11 ); however, the Ugandan estimate may have included persons who merely stayed in the same house as a patient without reporting physical contact. The secondary and tertiary attack risks in our study were found to be virtually identical, 21% and 19%, respectively; thus no evidence suggested that Marburg virus loses infectivity by repeated passages through humans.…”
Section: Discussionsupporting
confidence: 77%
“…Transmission between humans occurs through direct contact with symptomatic MHF patients or with their body fluids or remains ( 4 ). The risk for transmission of Marburg virus is assumed to increase with the intensity of physical contact and the amount of body fluids shed, as shown for Ebola virus ( 5 ). …”
mentioning
confidence: 99%
“…Although the region of endemicity of Ebola virus is limited, the risk of infection of humans and animals in other parts of the world is increasing with the increase in international traffic and transactions. Since Ebola virus causes secondary human-to-human infections among medical personnel and family members (2,20), it is important to diagnose the infection at the early stage of an outbreak and to alert society.On the basis of genetic divergence, four subtypes of Ebola viruses have been defined: subtypes Zaire, Sudan, Côte d 'Ivoire, and Reston (3,5,14). The first three subtypes cause severe clinical symptoms in both humans and monkeys, while subtype Reston has caused disease only in monkeys (4, 10, 11).…”
mentioning
confidence: 99%
“…Although the region of endemicity of Ebola virus is limited, the risk of infection of humans and animals in other parts of the world is increasing with the increase in international traffic and transactions. Since Ebola virus causes secondary human-to-human infections among medical personnel and family members (2,20), it is important to diagnose the infection at the early stage of an outbreak and to alert society.…”
mentioning
confidence: 99%
“…Aerosol is not thought to be the ordinary route of transmission in natural outbreaks; however, there have been reports of naive NHP infected across the room from experimentally infected NHP and human cases in which direct contact with infected patients could not be demonstrated, suggesting aerosol transmission [60,67,68]. Experimental studies have shown that filoviruses are relatively stable in aerosol, can survive on surfaces for prolonged periods of time, and are able to infect susceptible naive animals and cause lethal disease when inhaled [40][41][42][43][44]61,69,70].…”
Section: Animal Models Of the Human Diseasementioning
confidence: 99%